Alan Louis Smith's Vignettes: Covered Wagon Woman : a historical and musical analysis from a performer's perspective - Judge, Madeline (Royal Irish Academy of Music, 2023)
The history of art song in the United States is a varied and unique blend of differing styles and cultures. Previous research includes the histories of Native American music, the influence of mass immigration on American compositional sound and the study of the composers that have come to exemplify these blended traits of composition. With research contributions by Hugh Wiley Hitchcock, David Nichols and Charles Hiroshi Garrett, the history of American art song has been widely examined. A large amount of research has also explored performance practice and interpretation in art song, with a vast amount of analysis from Judith Carman, Thomas Hampson, and Victoria Etnier Villamill. Alan Louis Smith (b. 1955), is an American collaborative pianist and teacher, along with being a gifted composer. His contributions to American song present new investigations for research and deserve further examination. Smith combines his unique style of writing with song texts that derive from distinctive points in the history of the United States. While there has been research compiled on his other vocal works, such as Tamara Brook Regensburger’s dissertation ‘Alan Louis Smith’s Vignettes: Ellis Island: The history, evolution and performance of a modern American song cycle’, there are other works of his that deserve exploration. This thesis focuses on his song cycle, Vignettes: Covered Wagon Woman from the Daily Journal of Margaret Ann Alsip Frink 1850 for mezzo-soprano, violin and cello. Written for American mezzo-soprano, Stephanie Blythe, this thesis traces the origins of the work and explores the historical context of the diary, Smith’s compositional style, and the various implications for performers.
Keywords: Music; United States of America; Art song; Smith, Alan Louis. Vignettes: Covered Wagon Woman; Frink, Margaret A. (Margaret Ann) - Musical settings; Song cycles; Musical analysis; Performance practice (Music)